Determination of Nutritional and Antinutritional Characteristics of Ten Red Bean Cultivars (Phaseolus vulgaris L.) From Cameroon - Mananga, Marlyne-Josephine; Brice Didier, Kouandjoua; Charles, Kotue Taptue; Fadimatou, Bebbe; Ruth, Djuikwo Nkonga; Gilbert, Mbassi Manga; Blaise, Kuagny; Michelle, Djouhou; Elie, Fokou; Marie, Kana Sop (Emerging Challenges in Agriculture and Food Science Vol. 3, 2022)
Beans are nutritionally and economically important food crop in Cameroon. However, data on the nutritional value of the different red bean cultivars remain poorly known to consumers. The aim of the present study was to investigate the nutrients and the antinutrients content of both the raw and cooked ten red bean cultivars (Phaseolus vulgaris L.) from Cameroon. The moisture, lipid, protein, fibre, carbohydrate, ash contents and antinutrients composition were analysed using AOAC methods and minerals by atomic absorption spectrophotometry. Statistical analysis of the data was carried out using the ANOVA and the Tukey test (p \(≤\) 0.05). The results of chemical analysis of the raw and cooked cultivar bean revealed moisture content ranging from 4.19 to 12.34%, protein from 10.56 to 46%, lipids from 5.31 to 7.38%, ash from 1.93 to 4.61%, fiber from 2.42 to 7.97% and carbohydrates 38.30 to 68.85%. Different bean cultivars showed statistically significant differences in minerals. The most abundant minerals in the samples were potassium (K) and calcium (Ca) with contents ranging from 565.17 to 912.99 mg/100g dry matter (DM) and 78.5 to 933.85 mg/100g DM respectively. Iron (Fe) and zinc (Zn) contents ranged from 1.89 to 4.19 mg/100g DM and 2.10 to 5.15 mg/100g DM respectively. Antinutrients contents ranging from 0.14 to 1.00%, 2.86 to 8.82%, 0.07 to 0.18% and 0.26 to 1.22% respectively for tannins, phytates. oxalates and saponins after treatment. After soaking associated with cooking, red beans cultivars were found to contain the least minerals contents and that treatment significantly reduced (p<0.05) all the antinutrients evaluated. Red beans cultivars are potential nutrients rich food material for food formulation.